ANALISIS PENGARUH PERPUTARAN PERSEDIAAN, PERPUTARAN PIUTANG DAN PERPUTARAN ASET TETAP TERHADAP RASIO LANCAR Pada PT.Unilever Indonesia Tbk. Tahun 2013 – 2020 - NOVA ABRIANO; SETIAFITRIE YUNIARTI; SITI MUKARRAMAH (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, IAIN Fattahul Muluk Papua, 2021)
This study analyzes the effect of inventory turnover, receivables turnover, and fixed asset turnover on the current ratio at PT Unilever Indonesia at PT Unilever, Tbk in 2013-2020. This study uses quantitative research methods using data from the 2013-2020 quarterly financial statements. The results showed that the Inventory Turnover variable had a partially insignificant effect on the Current Ratio, the Accounts Receivable Turnover Variable had a partially significant effect on the Current Ratio, the Fixed Asset Turnover Variable had a partially insignificant effect on the Current Ratio. While the Inventory Turnover Variable, Variable Accounts Receivable Turnover, and Fixed Assets Turnover Variable together have no effect on the Current Ratio. This result is different from research by Nurjannah (2015) which shows that there is a significant positive effect between accounts receivable turnover, inventory turnover and cash turnover on the liquidity ratio partially or simultaneously. Keyword : Inventory Turnover, Receivables Turnover, Fixed Asset Turnover, Current Ratio